The detrimental effects of delay on the endorsement of misleading details for emotionally salient events - Shah, Datin; Knott, Lauren (Frontiers in Psychology, 2023)
Previous research has shown that the exposure to misleading information continues its detrimental effect on memory over time for negatively arousing events (Porter et al., 2010). However, research has also shown that both high- and low-arousing negative events are vulnerable to distortion from misinformation (Van Damme and Smets, 2014). Therefore, the present study set out to explore the impact of retention interval on memory for negative (arousing and non-arousing) and neutral events in the misinformation paradigm. Participants were presented with a negative high-arousing, a negative low-arousing, and a neutral scene, and exposed to misleading information for central and peripheral aspects of each scene. Recognition memory for scene details was measured 10 minutes after misinformation exposure and again after one week. We found that, regardless of the type of detail, the effect of misinformation persisted over time for the negative-arousing event but disappeared one week later for the negative low-arousing and neutral events. The results are explained in relation to adaptive function and theories of source monitoring. The findings of this study provide important forensic implications, especially when we consider the arousing nature of crimes.